Digital Transformation Of Procurement In Construction Industry In Sarawak - Muhammad Aiman, Rasidi (Universiti Malaysia Sarawak (UNIMAS), 2022)
The rise of internet technology has resulted in new and cost-effective methods, as well as numerous inventive apps that corporate companies can use. Using internet technology as a form of procurement for business-to-business transactions, also known as Electronic Procurement, is a critical commercial application (e-procurement). It is involve the using of electronic catalogue and automated workflow processes in procurement method. Construction industry in one of industries that require this e-procurement process. In Malaysia, this industry is one of the largest networks of supply chain from the clients, the consultants, contractors, suppliers, manufactures, the financier, insurance institutions and the consumers. The objective of conducting this research is to analyse the implementation of e-procurement and to identify the scope of e-procurement that be implement in Sarawak. The method used for this research in Quantitative Methodology. A set of questionnaire has been distribute to developer in Sarawak. All the outcomes from this research has been documented for future use. This paper has find that the level of adoption towards e-procurement in construction industry in Sarawak are not fully implement and this can contribute in expanding construction industries’ motivation to embark on e-procurement endeavour.